Anti-inflammatory compounds and a new sesquiterpene lactone from Centaurea gabrieljanae Greuter - Yildirim, Aybeniz; Sen, Ali; Bitis, Leyla (Taylor & Francis Ltd, 2025)
The traditional use of Centaurea spp. for anti-inflammatory purposes is widespread among the people in Turkiye. For this, the methanol extract of Centaurea gabrieljanae and sub-fractions of the methanol extract were tested for anti-inflammatory activity using 5-LOX, while their antioxidant activities, total phenol, and total flavonoid contents were also examined. The ethyl acetate fraction exhibited potent anti-inflammatory activity (IC50 = 3.864 +/- 0.9 mu g/ml), from which five known compounds (astragalin, picein, p-hydroxy benzoic acid, 3,4-dimethoxy-cinnamic acid, 4-hydroxybenzoic acid 4-O-beta-glucopyranoside) and a new sesquiterpene lactone named Pterochlorin were obtained. Pterochlorin showed potent anti-inflammatory activity with a value of IC50 12.71 +/- 0.7 mu g/ml compared to standard indomethacin. Similarly, astragalin was found to be strong (IC50 = 18.23 mu g/ml). In addition, 4-hydroxybenzoic acid 4-O-beta-glucopyranoside was isolated for the first time in Centaurea species, and its anti-inflammatory activity was tested. This study may be a guide for the discovery of a new anti-inflammatory drug derived from natural sources.
Keywords: Centaurea gabrieljanae; anti-inflammatory; sesquiterpene lactone; flavonoid